The new functional products inclusion in the complex rehabilitation and preventive programs in athletes with musculoskeletal disorders - V. N. Sergeev; O. M. Musaeva; A. S. Dydykin; M. A. Aslanova; A. V. Tarasov; A. V. Smolenskiy (National Electronic Information Consortium (NEICON), 2021)
The review presents an urgent problem of modern sports medicine - the development and inclusion of new nutritive and metabolic food products in the treatment of athletes with injuries and diseases of the musculoskeletal system. The analysis of the main etiological factors of the musculoskeletal disorders in athletes is presented. The study of the anatomical, histological and functional features of the bone-cartilaginous structures in athletes made it possible to establish the priority macro- and micronutrients, which should be the basis in modern specialized and functional food products. Brief composition characteristics of the new canned food "Enmit-beef" and dry protein concentrate "Ostov" (for the drink preparation) are presented. The preliminary results of the use of these functional meat-based products indicate their effectiveness in rehabilitation and treatment of athletes with musculoskeletal disorders.